EUFOREA/EPOS2020 statement on the clinical considerations for chronic rhinosinusitis with nasal polyps care - Hellings, Peter W; Alobid, Isam; Anselmo-Lima, Wilma T; Bernal-Sprekelsen, Manuel; Bjermer, Leif; Caulley, Lisa; Chaker, Adam; Constantinidis, Jannis; Conti, Diego M; De Corso, Eugenio; Desrosiers, Martin; Diamant, Zuzana; et al. (Allergy, 2024)
Following the European Forum for Research and Education in Allergy and Airway Diseases (EUFOREA) treatment algorithm for chronic rhinosinusitis (CRS) with nasal polyps (CRSwNP), patients suffering from severe uncontrolled CRSwNP are recommended to receive oral corticosteroids, (revision) sinus surgery, systemic biologicals and/or aspirin treatment after desensitization (ATAD). Given the major differences in indications, outcomes, practical considerations, risks and costs of these key pillars of treatment, there is a growing need to define criteria for each treatment option and list the clinically relevant and major considerations for them. This EUFOREA document therefore provides an expert panel overview of the expected outcomes, specific considerations and (contra)indications of the five major treatment arms of severe uncontrolled CRSwNP: oral corticosteroids, primary and revision sinus surgery, biological treatment and ATAD. This overview of treatment considerations is needed to allow physicians and patients to consider the different options in the context of providing optimal and personalized care for severe uncontrolled CRSwNP. In conclusion, the five major treatment options for severe uncontrolled CRSwNP have intrinsic advantages, specific indications and considerations that are of importance to the patient, the physician and the society. This EUFOREA statement supports the unmet need to define criteria for the indication of every treatment pillar of CRSwNP.
Keywords: Chronic Disease; nosní polypy; sinus surgery; management nemoci; CRSwNP; aspirin intolerance; Humans; corticosteroids; rinosinusitida; lidé; chronická nemoc; Rhinosinusitis; Disease Management; biologics; Nasal Polyps